The Measurement of Labor Force Dynamics with Longitudinal Data: The Labour Market Activity Survey Filter - Riddell, W. Craig (Journal of Labor Economics, 1995)
This article explores the measurement of labor force dynamics using longitudinal data, focusing in particular on the Canadian Labour Market Activity Survey (LMAS), which represents a potential advance in longitudinal data collection because it measures aspects of dynamics not available in existing panel data such as the Panel Study of Income Dynamics and the National Longitudinal Survey. We examine the implications of the LMAS questionnaire structure-the LMAS filter-for the study of labor market dynamics and undertake simulations to provide a quantitative assessment of the importance of this filter for labor force spells and transitions between labor force states.